Increased The Adolescent Self-Identity Using The Peplau-Erickson-Stuart Model - Eni Hidayati; Novy Helena Catharina Daulima; Ice Yulia Wardani (South East Asia Nursing Research, 2019)
Without proper stimulation, self-identity formation in adolescents may lead to inferiority, and further to the mental health problem. It is important to give positive stimulation for adolescents and psychoeducation for the family properly and effectively to improve adolescence identity development. As we know, adolescence is a period of age which is considered to be problematic and crucial for them to set their remarkable foundation regarding the interaction with the surrounding people and environment. This research was aimed to find out the result of therapeutic group therapy for adolescent and family psychoeducation toward the improvement of adolescence development. A case report was used as the method of the research, in which 5 clients were given health education care according to the problem faced by the family during the adolescence development stimulation. The special therapy given was the adolescence therapeutic group therapy and family psychoeducation. The result of therapeutic group therapy is the ability to improve family and adolescence self-identity development within the 10 aspects of adolescence stage; biological, psychosexual, cognitive, language, moral, spiritual, emotional, psychosocial, talent, and creativity. The result of the research was expected to be an input for the Department of Health, especially for the administrator of the community health program in dealing with adolescence mental problems. The research is also expected to be the evidence-based practice in the community of mental health nursing.